A systematic review of EFL research on the impact of reading comprehension on students’ vocabulary retention, and the relation between reading and vocabulary size - Binhomran, Kholoud; Altalhab, Sultan (International Journal of Language and Literary Studies, 2023)
This paper is a systematic review of studies conducted in the past two decades that addressed the effect of EFL reading comprehension on vocabulary retention, and the relation between reading and vocabulary size. Twenty-seven studies linking reading comprehension to a positive impact on EFL students’ retention and vocabulary size were identified for inclusion. The analysis confirmed four major relationships: (1) learning vocabulary by reading supported participants’ comprehension in almost all cases; (2) reading before engaging in vocabulary tasks supported participants’ word retention in almost all cases; (3) repetition is crucial for enhancing new vocabulary recall, but the vocabulary should be introduced contextually; (4) there is limited evidence that EFL learners should cover 98% of the text to understand the vocabulary. However, some studies showed that reaching the lexical threshold required for reading is not necessary if the learner has covered enough frequent suffixes of word families to provide them with a basic coverage of the text.